Institutional quality and foreign direct investment in ASEAN - Masron, Tajul Ariffin; Niaz Ahmad, Mohd Naseem (Faculty Economics & Administration, University of Malaya, 2017)
This study aims to investigate the role of institutional quality in influencing foreign direct investment. It employs two-stage least squares (2SLS) regression analysis to minimise the risk of bias due to endogeneity issue. Institutional quality is proxied by its ratio and gap to capture simultaneous changes in institutional quality of two countries under study. The results show that institutional quality matters for foreign direct investment. More importantly, although ratio of institutional quality is statistically significant, the actual improvement in host country’s institutional quality still depends on the changes in the competing country’s institutional quality. In other words, changes in the country’s institutional quality must be significantly greater than that of the competing country to assure that host country’s changes can be attractive for foreign direct investment. It should be cautioned that institutional quality is a necessary but not a sufficient precondition to attract FDI.